Analyzing Urbanization in Indonesia and Netherlands Through IDIC and Relationship Models - Arindhani, Amira; Amrullah, Azzahra Chadijah; Gunawan, Purbasari Nuasri; Schade, Luc (Institut Komunikasi dan Bisnis LSPR, 2025)
Urbanization is one of the most significant global megatrends according to the United Nations (UN) that can shape the future of societies. Jakarta is a city that has become the main destination for people from the rural areas to migrate. Despite facing many urban challenges, Jakarta still maintained its positive reputation as a symbol of hope and opportunity for the migrants while the Netherlands took a decentralized urban approach. The ecosystem applied the same with different cities such as Amsterdam, Rotterdam, Utrecht, and The Hague. This paper aims to find out how a city’s image can affect urbanization by comparing urbanization conditions in Jakarta with cities in the Netherlands, as well as how their governments manage its relationship with their citizens through the lens of two frameworks such as 7 Relationship Characteristics as well as the IDIC Model from Peppers and Rogers (2017). This study uses a qualitative comparative case study approach, where the data gained for this research was collected through available public sources. In conclusion, the findings of this research show how both sides offer a different reputation, with Jakarta being a “powerhouse” of the nation, whilst the Netherlands showcased the benefits of equal distribution of economic development.